Antimicrobial Photodynamic Therapy Involving a Novel Photosensitizer Combined With an Antibiotic in the Treatment of Rabbit Tibial Osteomyelitis Caused by Drug-Resistant Bacteria - Yin, Xiujuan; Fang, Ziyuan; Fang, Yan; Zhu, Lin; Pang, Jinwen; Liu, Tianjun; Zhao, Zhanjuan; Zhao, Jianxi (Frontiers in Microbiology, 2022)
Osteomyelitis is deep tissue inflammation caused by bacterial infection. If such an infection persists, it can lead to dissolution and necrosis of the bone tissue. As a result of the extensive use of antibiotics, drug-resistant bacteria are an increasingly common cause of osteomyelitis, limiting the treatment options available to surgeons. Photodynamic antibacterial chemotherapy has attracted increasing attention as a potential alternative treatment. Its advantages are a broad antibacterial spectrum, lack of drug resistance, and lack of toxic side effects. In this study, we explored the impact of the new photosensitizer LD4 in photodynamic antimicrobial chemotherapy (PACT), both alone and in combination with an antibiotic, on osteomyelitis. A rabbit tibial osteomyelitis model was employed and microbiological, histological, and radiological studies were performed. New Zealand white rabbits (n = 36) were randomly divided into a control group, antibiotic group, PACT group and PACT + antibiotic group for treatment. In microbiological analysis, a reduction in bacterial numbers of more than 99.9% was recorded in the PACT group and the PACT + antibiotic group 5 weeks after treatment (p < 0.01). In histological analysis, repair of the damaged bone tissue was observed in the PACT group, and bone repair in the PACT + antibiotic group was even more significant. In radiological analysis, the X-ray Norden score showed that the severity of bone tissue defects or destruction followed the pattern: PACT + antibiotic group < PACT group < antibiotic group < control group.